Pengaruh Praktek Kerja Nyata dan Sarana Pembelajaran Praktek terhadap Kesiapan Kerja Mahasiswa Jurusan Manajemen Perhotelan Sekolah Perhotelan Bali pada Industri Pariwisata - I Nyoman Sudiarta (Institut Pariwisata dan Bisnis Internasional, 2012)
The aims of this research are to find out: (1) the effect of the job training and practical learning facilities simultaneously to working readiness of students (2) The effect of the job training and practical learning facilities partially to working readiness of students (3) the dominant effect between on the job training and practical learning facilities to working readiness of students.The samples of this research are all students of Hotel Management Program at The Bali Hotel School in the academic year 2010/2011. The total number of the samples are Â 87 students. Out of those 87 students, there are only 84 students return and answer the questionnaires. The data of each variable was analyzed by means of descriptive statistical analysis to find out any trend appearing in each variable and to explore the significant relation between the independent and dependent variable, both simultaneously and partially. The analysis applied for this is partial correlation and multiple regression analysis.The results of quantitative analysis show that: (1) there wasÂ significant effect simultaneously between on the job training and practical learning facilities to working readiness of student based on the analysis of F test with SPSS program version 17 found the value of counted F is 90,343 and Sig value is 0,000. (2) There was significant effect partially between on the job training and practical learning facilities to working readiness of students based on the analysis of t test found significant of > 0,05. (3) The variable having dominant effect to working readiness of student is practical learning facilities (X2) which has the beta value of 0,558 while on the job training (X1) has the beta value of 0,292.